Vulnerability and the Politics of Care Transdisciplinary Dialogues - Browne, Victoria; DANELY, Jason; Rosenow, Doerthe (Oxford University Press, 2021)
Vulnerability is a fundamental aspect of existence, giving rise to the need for care in various forms. Yet we are not all vulnerable in the same way, and not all vulnerabilities are equally recognised or cared for. This transdisciplinary volume considers how vulnerability and care are shaped by relations of power within contemporary contexts of war, development, environmental degradation, sexual violence, aging populations and economic precarity. It proposes that care for vulnerable populations or individuals is inseparable from other political processes of recognition, welfare, healthcare and security, whilst also exploring vulnerability as a shared, generative condition that makes caring possible. Ethnographic and narrative accounts of vulnerable life and caring relations in various geographical regions - including Japan, Uganda, Micronesia, Iraq, Mexico, the UK and the US - are interspersed with perspectives from philosophy, International Relations, social and cultural theory, and more, resulting in a compelling series of intellectual exchanges, creative frictions and provocative insights.